2014
DOI: 10.4103/0972-6748.151679
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study of self-reported ADHD symptoms and psychological comorbidity among college students in Chandigarh, India

Abstract: Background:Existence of attention deficit hyperactivity disorder (ADHD) in adults is scantily researched in India. There is dearth of information on prevalence of ADHD in college students worldwide. Further, fewer studies in the past have evaluated the impact of ADHD on the psychological well-being of college students.Aims:To study the prevalence of ADHD among college students and psychological problems related to ADHD.Design:Cross-sectional study.Subjects and Methods:A total of 237 students were recruited fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
(32 reference statements)
0
11
0
Order By: Relevance
“…In India, prevalence of ADHD was reported to be 11.33% among primary school children [22], 7.2% among adolescents [23], and 5.48% among college students [24]. However, detailed report on birth histories and their possible influence on the symptom severity were less frequently studied.…”
Section: Discussionmentioning
confidence: 99%
“…In India, prevalence of ADHD was reported to be 11.33% among primary school children [22], 7.2% among adolescents [23], and 5.48% among college students [24]. However, detailed report on birth histories and their possible influence on the symptom severity were less frequently studied.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] A study recruiting 237 college students in Chandigarh reported an even lower rate of with 13 (5.48%) qualifying for the diagnosis of adult ADHD. [ 15 ] The authors note that there is a paucity of studies in larger community samples across wider age groups in India.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of 25.7% on the critical items scale compares well with the 23.6% prevalence among college students of Chandigarh by Jhambh et al . [ 8 ] and the 21.8% among Kenyan University students by Atwoli et al . [ 9 ] However, the studies done in Chandigarh and Kenya used the full ASRS scale (49.3% prevalence in our study).…”
Section: Discussionmentioning
confidence: 99%